COST OF AERIAL AND GROUND SPRAYINGS AND TECHNOLOGICAL REPLACEMENT POINT: A CASE STUDY IN THE REGION OF MINEIROS, GO, BRAZIL - Moraes, Tiago R. [UNESP]; Cornago, Vicente M. [UNESP]; Araújo, Vitor C. R. De [UNESP]; Esperancini, Maura S. T. [UNESP]; Antuniassi, Ulisses R. [UNESP] (Associação Brasileira de Engenharia Agrícola, 2021)
One of the main costs in agriculture is related to mechanized operations, which, in turn, are associated with the capital invested in machinery and equipment, the scale of production, and the operating efficiency. Thus, the choice of technology to carry out these operations must take these factors into account to minimize the production cost. In this context, this study aimed to evaluate the most economical investment option for the set of sprayings on a farm located in the municipality of Mineiros, Goiás, Brazil, by comparing two technologies (ground and aerial spraying) and identifying the scale of production that makes each of the technologies more feasible. This study covers the period of one year with the soybean crop in the summer season, followed by the cultivation of corn in the off-season. Economic feasibility indicators were calculated, and the total average costs of both technologies were compared. The results allowed concluding that the investment in aerial spraying with the aircraft acquisition is assertive, as it reduced losses due to crushing. Contracting the service via third parties is feasible and can be used not only in cases of emergency, as it allows for increased profitability.
Keywords: Efficiency; pesticide spraying; plant crushing; application costs; productivity